An Ontology-Driven Adaptive User Interface Framework for Indonesian Student Wellbeing - Bhanu Sri Nugraha; Muhammad Suyanto; Kusrini Kusrini; Ema Utami (Universitas Nusantara PGRI Kediri, 2026)
Background: The personalization of digital learning environments to support student wellbeing presents a significant challenge due to the need for integrating multi-dimensional contextual factors. Existing adaptive user interface (AUI) approaches often rely on ad-hoc rule-based systems or simpler adaptive mechanisms, lacking the formal semantic grounding required to handle the intricate interdependencies between diverse wellbeing dimensions and corresponding UI adaptations. Objective: This research aimed to design, develop, and formally validate a novel semantic framework for a context-aware AUI specifically tailored to provide a formal foundation for supporting multidimensional student wellbeing factors. Methods: The methodology involved creating a detailed